Assessing the impact of digital enablement on internal brand management in higher education institutions - Urooj, Ahmed; Rukhsar, Ahmed; Sharizal, Hashim; Mahani, Mohammad Abdu Shakur; Areej, Ahmed (Springer Nature, 2026)
In today’s competitive higher education landscape, developing a strong and consistent brand image that embraces digital enablement is crucial for improving employee brand relationships. Technological advancements, particularly digital, can significantly enhance an organization’s brand positioning. However, research on the role of digital enablement in employee brand relationship formation, especially in higher education institutions (HEIs), is limited. This study, grounded in Social Exchange Theory, investigates the impact of internal brand management— comprising communication, training, and leadership—on Employee Brand Relationship Quality (EBRQ) and examines the moderating role of digital enablement within HEIs. Utilizing a sample of 372 employees from HEIs in Pakistan and employing Smart PLS-SEM 4 for data analysis, the study reveals that only training and leadership significantly influence employee-university brand relationship quality, with digital enablement playing a significant moderating role. This highlights the importance of digital enablement in enhancing collaboration, human development, and aligning employee perceptions and behaviors with the organization’s brand. The findings support institutional efforts aligned with the United Nations Sustainable Development Goals, particularly SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth), by promoting digitally enabled and employeecentered brand development in higher education. This research offer a nuanced understanding of the complex relationships between brand management and technological innovation from the internal customer perspective.